Strategi Strategi Pembelajaran Baca Tulis Al-Qur'an di Sekolah Inklusi: Pembelajaran Baca Tulis Al-Qur'an di Sekolah Inklusi - Rohmah, Meiza Miftachul; Sopian, Asep; Sauri, Sofyan (Jurusan Pendidikan Luar Biasa, 2021)
Every human being is essentially the same, obtaining the same rights and opportunities in various ways including obtaining education for the sustainability of his life regardless of race, ethnicity, gender, culture or religion. Similarly with children with special needs, therefore school inclusion is an answer that education is not a discrimination. Inclusion schools are schools that mix children with special needs with other normal children to learn and interact together. Children with special needs hold different perspectives in understanding a subject. Therefore, this article aims to discuss what strategies are suitable for children with special needs with slow learner and speech delay categories in order to achieve educational goals. Descriptive research with a qualitative approach is the method that researchers will use in this study. Data collection techniques used observation and documentation. This study shows that learners with special needs tend to easily understand the subject matter through things that learners like movies. However, keep in mind that children with special needs have different characteristics and cannot be generalized. Therefore, to find the right learning strategy teachers must conduct initial activities through observation of students with special needs.